Development of tourist travel pattern mathematically in Spermonde islands, South Sulawesi, Indonesia - Amirullah, Amirullah; Rusdi, Muhammad; Sarira, Matthew Tinna; Djabbar, Atriana; Hanafi, Hasdar; Sudrajat, Yayan (SAINTIS Publishing, 2023)
Travel patterns destination Region Loop, or a combination of Single Point and Chaining Loopused to go to zone A, zone B, zone C and zone D in the Spermonde archipelago for the purpose of marine tourism activities relation to activities at sea, both above sea level (marine) and activities carried out below sea level (submarine).